Orthodontıc Treatment Of Unılateral Cleft Lıp And Palate: A Case Report - İlken Kocadereli; İçim Kavuklu (Galenos Yayinevi, 2001)
Cleft lip and palate is the most common malformation in the craniofacial region. There can be few conditions that require the expertise of so many specialists from birth to maturity. The treatment of cleft lip and palate malformation is a teamwork, which requires the expertise of so many specialists from birth to maturity. The child with a cleft lip and palate will almost always require orthodontic treatment in the late mixed and permanent dentition. Here, orthodontic treatment of unilateral cleft lip and palate patient is presented.